Kontribusi Filantropi Islam (ZISWAF) dalam Mendukung Pembangunan Ekonomi Berkelanjutan SDGs - Rahmat Firdaus (ZAWA: Management of Zakat and Waqf Journal, 2025)
Islamic philanthropy plays an important role in promoting sustainable economic development through various instruments such as zakat, infaq, sedekah, and waqf. This concept is based on the principle of social justice and equitable distribution of wealth, which aims to reduce economic disparities and improve people's welfare. In relation to sustainable development, Islamic philanthropy makes significant contributions in various key sectors, including education, health, economic empowerment, and environmental conservation. The use of digital technology increasingly increases efficiency in the management of philanthropic funds, creating transparency and wider access for beneficiaries. This article examines the role of Islamic philanthropy in achieving the Sustainable Development Goals (SDGs) as well as the challenges and opportunities in optimizing its contribution. By adopting a more innovative and collaborative approach, Islamic philanthropy has the potential to become a major driver in creating a more just, inclusive, and sustainable economy.